Acetylation Rather than H50Q Mutation Impacts the Kinetics of Cu(II) Binding to α‐Synuclein. Issue 23 (14th October 2021) - Teng, Xiangyu; Sheveleva, Alena; Tuna, Floriana; Willison, Keith R.; Ying, Liming
Abstract: The interaction between α‐synuclein (αSyn) and Cu 2+ has been suggested to be closely linked to brain copper homeostasis. Disruption of copper levels could induce misfolding and aggregation of αSyn, and thus contribute to the progression of Parkinson's disease (PD). Understanding the molecular mechanism of αSyn‐Cu 2+ interaction is important and controversies in Cu 2+ coordination geometry with αSyn still exists. Herein, we find that the pathological H50Q mutation has no impact on the kinetics of Cu 2+ binding to the high‐affinity site of wild type αSyn (WT‐αSyn), indicating the non‐involvement of His50 in high‐affinity Cu 2+ binding to WT‐αSyn. In contrast, the physiological N‐terminally acetylated αSyn (NAc‐αSyn) displays several orders of magnitude weaker Cu 2+ binding affinity than WT‐αSyn. Cu 2+ coordination mode to NAc‐αSyn has also been proposed based on EPR spectrum. In addition, we find that Cu 2+ coordinated WT‐αSyn is reduction‐active in the presence of GSH, but essentially inactive towards ascorbate. Our work provides new insights into αSyn‐Cu 2+ interaction, which may help understand the multifaceted normal functions of αSyn as well as pathological consequences of αSyn aggregation. Abstract : Understanding the molecular mechanism of αSyn‐Cu 2+ interaction : From a kinetic perspective, His50 of αSyn is irrelevant to high‐affinity Cu 2+ binding, while N‐terminal acetylation attenuates Cu 2+ binding affinity of αSyn around four orders of magnitude. Reduction kinetics of Cu 2+ coordinated αSyn is also reported.